An algorithm for embedding oversubscribed virtual data center - Chukun LU; Fangfang YAN; Dong LI (Dianxin kexue)
Predictable network performance is critical for cloud applications and can be achieved by providing tenants a dedicated virtual data center (VDC) with bandwidth guarantee.The embedding problem of oversubscribed data center in physical data center network was studied.Compared with the general virtual data center,the traffic pattern between the virtual machines in the over-subscription virtual data was more complicated.Therefore,the flow model and the embedding problem were described.A heuristic algorithm with lower time complexity was proposed for the embedding problem of virtual machine-packet perturbation algorithm.Finally,the simulation algorithm was used to compare the packet perturbation algorithm with the algorithm proposed in the previous work and the famous first-fit.The experiment result shows that the proposed algorithm improves the embedding success rate while reducing the complexity of the algorithm.